A method for preparing dysprosium oxide / nitrogen-defective graphite phase carbon nitride visible light catalyst

By constructing a heterojunction with doped nitrogen-deficient graphite phase carbon nitride and dysprosium oxide, a visible photocatalyst of dysprosium oxide/nitrogen-deficient graphite phase carbon nitride is prepared, which solves the problem of low efficiency of decomposing water under visible light to form hydrogen, and achieves a higher photocatalytic hydrogen production efficiency.

CN116943700BActive Publication Date: 2025-04-08SHANDONG UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310667579.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-07
Publication Date
2025-04-08
Estimated Expiration
2043-06-07

AI Technical Summary

Technical Problem

The existing single semiconductor photocatalysts have low efficiency in decomposing water under visible light to produce hydrogen, mainly due to the large band gap width and the high electron-hole pair recombination rate, resulting in a small light absorption range and a low charge separation rate.

Method used

Heterojunction is constructed by doping nitrogen-deficient graphite phase carbon nitride (ND-g-C3N4) and dysprosium oxide (Dy2O3), and a visible photocatalyst for dysprosium oxide/nitrogen-deficient graphite phase carbon nitride is prepared, which adjusts the band gap width of the semiconductor and reduces the recombination rate of photogenerated carriers.

Benefits of technology

The photocatalyst's response ability to visible light and the efficiency of photocatalytic hydrogen production are improved, the hydrogen production rate is significantly improved, and the synthesis method is simple and easy to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116943700B_ABST
    Figure CN116943700B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of semiconductor photocatalysts, and specifically relates to a method for preparing a dysprosium oxide / nitrogen-deficient graphite phase carbon nitride visible light catalyst. The preparation method includes the preparation of modified nitrogen-deficient graphite phase carbon nitride, the preparation of nitrogen-deficient graphite phase carbon nitride suspension, the mixing of nitrogen-deficient graphite phase carbon nitride suspension with dysprosium oxide, and the preparation of dysprosium oxide / graphite phase carbon nitride photocatalyst by calcination. In the modified ND‑g‑C3N4 prepared by the present invention, due to the presence of nitrogen defects, it has a smaller bandgap and a lower carrier recombination rate, and can construct a heterojunction with dysprosium oxide to adjust the band gap of dysprosium oxide, broaden the light response range, and make the dysprosium oxide / graphite phase carbon nitride visible light catalyst have a higher photocatalytic hydrogen production efficiency than dysprosium oxide itself, and its synthesis method is relatively simple, easy to operate, and can be synthesized in one step.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductor photocatalysts, and in particular relates to a method for preparing a dysprosium oxide / nitrogen-defective graphite phase carbon nitride visible light catalyst. Background Art

[0002] Due to the acceleration of urbanization and industrialization, energy shortage and environmental pollution are becoming increasingly serious. Hydrogen energy, as a clean energy with high calorific value, is considered to be the most ideal alternative to traditional fossil fuels. Using solar energy to decompose water to produce hydrogen is a low-cost, high-efficiency and promising method for hydrogen production. Since 43% of sunlight is in the visible light region, the research on water decomposition under visible light irradiation has certain practical significance.

[0003] The key to producing hydrogen by splitting water under visible light is to construct an efficient and stable photocatalyst. So far, various catalysts for photocatalytic hydrogen evolution have been explored, such as semiconductor photocatalysts such as titanium dioxide (TiO2), zinc oxide (ZnO), cadmium sulfide (CdS), and graphite carbon nitride (g-C3N4). However, these single semiconductor photocatalysts usually have problems such as large bandgap width and high electron-hole pair recombination rate, which makes their light absorption range small and the effective charge separation rate low, thus not having high visible light catalytic hydrogen production ability. The unpaired electrons in the inner 4f orbit of dysprosium oxide (Dy2O3) give it an electronic energy level, and the f shell captures excited electrons during visible light irradiation, further delaying the recombination process of electron-hole pairs. However, the photocatalytic activity of Dy2O3 is not high, mainly because of its large bandgap width, which can only absorb ultraviolet light, which accounts for only about 4% of sunlight, and has poor response to visible light, which greatly limits the research and development of dysprosium oxide in photocatalytic hydrogen production. Based on the above shortcomings, in order to improve the visible light catalytic efficiency of Dy2O3, the modification by coupling narrow bandgap semiconductors to form heterojunctions is a common solution. Graphitic carbon nitride (g-C3N4) has become one of the research hotspots in the field of photocatalysis because of its good stability, easy-to-regulate energy band structure, and low cost and availability. Defect engineering can adjust the bandgap structure of g-C3N4 and reduce the recombination rate of carriers, and is considered to be an effective strategy to improve its photocatalytic performance. The introduction of nitrogen defects can not only expand the light absorption range of g-C3N4, but also produce more effective electronic excitation, which is beneficial to charge transfer. Therefore, seeking a new method for preparing composite catalysts has become an urgent problem to be solved. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a dysprosium oxide / nitrogen-deficient graphite phase carbon nitride visible light catalyst, by doping nitrogen-deficient graphite phase carbon nitride (ND-g-C3N4) and constructing a heterojunction with dysprosium oxide, to prepare a semiconductor photocatalyst with excellent performance, adjust the band gap width of the semiconductor, reduce the recombination rate of photogenerated carriers, and thus improve the hydrogen production efficiency of the photocatalyst. The technical solution adopted is:

[0005] A method for preparing a dysprosium oxide / nitrogen-defective graphite phase carbon nitride visible light photocatalyst comprises the following steps:

[0006] (1) Preparation of modified nitrogen-deficient graphite carbon nitride (ND-g-C3N4): urea was dissolved in a certain volume of KOH aqueous solution and dried in an oven; the dried mixture was transferred to a crucible, calcined in a muffle furnace, cooled to room temperature naturally, washed three times with anhydrous ethanol and deionized water respectively, and placed in a vacuum drying oven to obtain modified ND-g-C3N4;

[0007] (2) preparing ND-g-C3N4 suspension: placing the ND-g-C3N4 obtained in step (1) in deionized water and uniformly dispersing it by ultrasonication to obtain ND-g-C3N4 suspension;

[0008] (3) Mixing: Add dysprosium oxide (Dy2O3) to the ND-g-C3N4 suspension, stir the mixture by ultrasonication to make it uniform, and then place the mixture in a vacuum drying oven to obtain a solid substance;

[0009] (4) Preparation of dysprosium oxide / graphite-phase carbon nitride photocatalyst by calcination method: The solid material obtained in step (3) is transferred to a porcelain boat and calcined in a tubular furnace to obtain a dysprosium oxide / nitrogen-deficient graphite-phase carbon nitride visible light catalyst.

[0010] Preferably, in step (1), the mass ratio of KOH to urea is (2-10):750, and the drying temperature is 60°C.

[0011] Preferably, the mass ratio of KOH to urea is 6:750.

[0012] Preferably, in step (1), the volume ratio of urea to KOH aqueous solution is 7.5 / 50 g / ml.

[0013] Preferably, in step (1), the calcination temperature is 550°C, the calcination time is 3h, the heating rate is 5°C / min, and the vacuum drying temperature is 55°C.

[0014] Preferably, in step (2) and step (3), the mass ratio of nitrogen-deficient graphite phase carbon nitride to dysprosium oxide is 1:2-19.

[0015] Preferably, in step (4), the heating rate of the tubular furnace is 5°C / min, the roasting temperature is 500°C, and the roasting time is 3h.

[0016] Preferably, in the prepared dysprosium oxide / nitrogen-deficient graphite-phase carbon nitride visible light photocatalyst, the mass percentage of nitrogen-deficient graphite-phase carbon nitride is 20-30%, especially 25%, and the photocatalytic hydrogen production efficiency is the highest.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The modified ND-g-C3N4 prepared by the present invention has a smaller bandgap and a lower carrier recombination rate due to the presence of nitrogen defects, and can construct a heterojunction with dysprosium oxide to adjust the band gap of dysprosium oxide and broaden the light response range, so that the dysprosium oxide / graphite phase carbon nitride visible light catalyst has a higher photocatalytic hydrogen production efficiency than dysprosium oxide itself. The synthesis method thereof is relatively simple and easy to operate, and can be synthesized in one step.

[0019] In the preparation method of the present invention, when the mass ratio of KOH to urea is 6:750 and the mass percentage of nitrogen-deficient graphite phase carbon nitride is 25%, the prepared dysprosium oxide / nitrogen-deficient graphite phase carbon nitride visible light photocatalyst is applied to photolysis of water, and the hydrogen production rate can reach 470 μmol·h -1 ·g -1 about. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The XRD spectra of the dysprosium oxide / nitrogen-defective graphite phase carbon nitride photocatalyst with varying KOH doping amounts prepared in the present invention are shown.

[0021] Figure 2 The XRD spectrum of the dysprosium oxide / nitrogen-deficient graphite phase carbon nitride photocatalyst with varying ND-g-C3N4 loadings prepared in the present invention.

[0022] Figure 3 This is a SEM image of the dysprosium oxide / nitrogen-defective graphite-phase carbon nitride photocatalyst prepared in Example 9 of the present invention.

[0023] Figure 4 The EPR spectra of graphite phase carbon nitride and nitrogen-defective graphite phase carbon nitride prepared in the present invention are shown.

[0024] Figure 5 The ultraviolet-visible diffuse reflectance spectra of dysprosium oxide / nitrogen-defective graphite phase carbon nitride with varying KOH doping amounts and pure dysprosium oxide prepared in the present invention.

[0025] Figure 6 The UV-visible diffuse reflectance spectra of dysprosium oxide / nitrogen-defective graphite phase carbon nitride with varying loading amounts of ND-g-C3N4 prepared in the present invention and pure dysprosium oxide.

[0026] Figure 7 The graph shows the hydrogen production of dysprosium oxide / nitrogen-defective graphite phase carbon nitride photocatalyst with varying KOH doping amounts prepared in the present invention and pure dysprosium oxide within 4 hours.

[0027] Figure 8 This is a graph showing the hydrogen production in 4 hours of the dysprosium oxide / nitrogen-defective graphite phase carbon nitride photocatalyst with varying loading amounts of ND-g-C3N4 prepared in the present invention and pure dysprosium oxide. DETAILED DESCRIPTION

[0028] The drawings are only used for illustrative purposes; for those skilled in the art, some well-known structures and their descriptions in the drawings may be omitted, and therefore, they should not be understood as limitations on the present invention.

[0029] The sources of the raw materials used in the present invention are not particularly limited and can be commercially available.

[0030] The technical solutions and effects of the present invention are described in detail below with reference to the accompanying drawings.

[0031] Example 1

[0032] A method for preparing a dysprosium oxide / nitrogen-defective graphite phase carbon nitride visible light photocatalyst comprises the following steps:

[0033] (1) Preparation of modified nitrogen-deficient graphite phase carbon nitride (ND-g-C3N4): 7.5 g of urea was dissolved in 50 ml of KOH aqueous solution, where the mass of KOH was 0.02 g.

[0034] Then it was placed in an oven at 60°C for drying, and the dried mixture was transferred to a crucible and calcined in a muffle furnace at a temperature of 550°C, a calcination time of 3h, and a heating rate of 5°C / min. After the calcination was completed, it was taken out and naturally cooled to room temperature. It was washed three times with anhydrous ethanol and deionized water respectively, and dried in a vacuum drying oven at 55°C to obtain modified ND-g-C3N4.

[0035] (2) Preparation of ND-g-C3N4 suspension: The ND-g-C3N4 obtained in step (1) is placed in deionized water and dispersed evenly by ultrasonication to obtain a ND-g-C3N4 suspension.

[0036] (3) Mixing: Add dysprosium oxide (Dy2O3) to the ND-g-C3N4 suspension, stir it by ultrasonic to make it mix evenly, and then place it in a vacuum drying oven to obtain a solid substance.

[0037] (4) Preparation of dysprosium oxide / graphite phase carbon nitride photocatalyst by calcination method: The solid material obtained in step (3) is transferred to a porcelain boat and calcined in a tube furnace to obtain a dysprosium oxide / nitrogen-deficient graphite phase carbon nitride visible light catalyst. The mass ratio of nitrogen-deficient graphite phase carbon nitride to dysprosium oxide is 1:19, that is, the mass fraction of ND-g-C3N4 in the prepared catalyst is 5%, marked as Dy2O3-5%CN-0.02.

[0038] Example 2

[0039] 7.5 g of urea was dissolved in 50 ml of KOH aqueous solution, wherein the mass of KOH was 0.04 g. In the prepared catalyst, the mass fraction of ND-g-C3N4 was 5%, and it was marked as Dy2O3-5%CN-0.04. Other parts not mentioned were the same as those in Example 1.

[0040] Example 3

[0041] 7.5 g of urea was dissolved in 50 ml of KOH aqueous solution, wherein the mass of KOH was 0.06 g. In the prepared catalyst, the mass fraction of ND-g-C3N4 was 5%, and it was marked as Dy2O3-5%CN-0.06. Other parts not mentioned were the same as those in Example 1.

[0042] Example 4

[0043] 7.5 g of urea was dissolved in 50 ml of KOH aqueous solution, wherein the mass of KOH was 0.08 g. In the prepared catalyst, the mass fraction of ND-g-C3N4 was 5%, and it was marked as Dy2O3-5%CN-0.08. Other parts not mentioned were the same as those in Example 1.

[0044] Example 5

[0045] 7.5 g of urea was dissolved in 50 ml of KOH aqueous solution, wherein the mass of KOH was 0.1 g. In the prepared catalyst, the mass fraction of ND-g-C3N4 was 5%, and it was marked as Dy2O3-5%CN-0.1. Other parts not mentioned were the same as those in Example 1.

[0046] Implementation 6

[0047] A method for preparing a dysprosium oxide / nitrogen-defective graphite phase carbon nitride visible light photocatalyst comprises the following steps:

[0048] (1) Preparation of modified nitrogen-deficient graphite phase carbon nitride (ND-g-C3N4): 7.5 g of urea was dissolved in 50 ml of KOH aqueous solution, where the mass of KOH was 0.06 g.

[0049] Then it was placed in an oven at 60°C for drying, and the dried mixture was transferred to a crucible and calcined in a muffle furnace at a temperature of 550°C, a calcination time of 3h, and a heating rate of 5°C / min. After the calcination was completed, it was taken out and naturally cooled to room temperature. It was washed three times with anhydrous ethanol and deionized water respectively, and dried in a vacuum drying oven at 55°C to obtain modified ND-g-C3N4.

[0050] (2) Preparation of ND-g-C3N4 suspension: The ND-g-C3N4 obtained in step (1) is placed in deionized water and dispersed evenly by ultrasonication to obtain a ND-g-C3N4 suspension.

[0051] (3) Mixing: Add dysprosium oxide (Dy2O3) to the ND-g-C3N4 suspension, stir it by ultrasonic to make it mix evenly, and then place it in a vacuum drying oven to obtain a solid substance.

[0052] (4) Preparation of dysprosium oxide / graphite phase carbon nitride photocatalyst by calcination method: The solid material obtained in step (3) is transferred to a porcelain boat and calcined in a tube furnace to obtain a dysprosium oxide / nitrogen-deficient graphite phase carbon nitride visible light catalyst. The mass ratio of nitrogen-deficient graphite phase carbon nitride to dysprosium oxide is 1:9, that is, the mass fraction of ND-g-C3N4 in the prepared catalyst is 10%, and the label is Dy2O3-10%CN-0.06.

[0053] Example 7

[0054] The mass ratio of nitrogen-deficient graphite phase carbon nitride to dysprosium oxide used is 3:17, that is, the mass fraction of ND-g-C3N4 in the prepared catalyst is 15%, marked as Dy2O3-15%CN-0.06. Other parts not mentioned are the same as Example 6.

[0055] Example 8

[0056] The mass ratio of nitrogen-deficient graphite phase carbon nitride to dysprosium oxide used is 1:4, that is, the mass fraction of ND-g-C3N4 in the prepared catalyst is 20%, marked as Dy2O3-20%CN-0.06. Other parts not mentioned are the same as Example 6.

[0057] Example 9

[0058] The mass ratio of nitrogen-deficient graphite phase carbon nitride to dysprosium oxide used is 1:3, that is, the mass fraction of ND-g-C3N4 in the prepared catalyst is 25%, marked as Dy2O3-25%CN-0.06, such as Figure 3 The SEM image of the prepared catalyst is shown in FIG.

[0059] Example 10

[0060] The mass ratio of nitrogen-deficient graphite phase carbon nitride to dysprosium oxide used is 3:7, that is, the mass fraction of ND-g-C3N4 in the prepared catalyst is 30%, marked as Dy2O3-30%CN-0.06. Other parts not mentioned are the same as Example 6.

[0061] Comparative Example 1

[0062] The suspension of unmodified graphite phase carbon nitride (g-C3N4) was prepared, ultrasonically dispersed, dysprosium oxide (Dy2O3) was added, ultrasonically stirred to mix evenly, and then placed in a vacuum drying oven to obtain a solid substance, and the dysprosium oxide / graphite phase carbon nitride photocatalyst was prepared by calcination, the mass fraction of g-C3N4 in the prepared catalyst was 5%, and it was marked Dy2O3-5%CN-0. Other places not mentioned are the same as Example 1.

[0063] like Figure 1 As shown, Dy2O3 has characteristic peaks at 2θ=20.32°, 29.04°, 33.64°, 43.25°, 48.36°, and 57.32°, which correspond to the (211), (222), (400), (134), (400), and (622) crystal planes of cubic phase Dy2O3 (JCPDS card: NO.78-0388). The characteristic peaks of Dy2O3-5%CN-x sample are basically the same as those of Dy2O3, and it is difficult to find the characteristic peaks of ND-g-C3N4, indicating that the content of ND-g-C3N4 is very small and its crystal structure is not changed during the preparation process.

[0064] like Figure 2 As shown, for the prepared catalyst, it is observed that with the increase of CN-0.06 content, the position of the characteristic peak of Dy2O3 in the prepared catalyst is the same as that of pure Dy2O3, indicating that the addition of CN-0.06 does not change the crystal form of Dy2O3. When the addition amount of CN-0.06 is 25% and 30%, the peak intensity of Dy2O3 in the prepared catalyst gradually weakens, which may be due to the increase in the content of CN-0.06, the increase in the amount of CN-0.06 on the surface of Dy2O3, and the decrease in the crystallinity of Dy2O3. At the same time, in the prepared catalysts Dy2O3-20%CN-0.06, Dy2O3-25%CN-0.06, and Dy2O3-30%CN-0.06, a weaker (002) diffraction peak corresponding to CN-0.06 was observed at 27.53°, which is attributed to the higher dispersibility and lower crystallinity of CN-0.06. The remaining diffraction peaks are consistent with Dy2O3 (JCPDS card: NO.78-0388), proving that the composite material is composed of Dy2O3 and CN-0.06.

[0065] like Figure 3As shown, from the scanning electron micrograph of the prepared catalyst, it can be seen that ND-g-C3N4 is evenly dispersed among Dy2O3, but the original rod-like structure of Dy2O3 is not destroyed. The two substances are closely distributed, indicating that the catalyst prepared by Dy2O3 / ND-g-C3N4 has been successfully synthesized.

[0066] like Figure 4 As shown, both ND-g-C3N4 and g-C3N4 show a single Lorentzian line with a g value of 2.004. Among them, ND-g-C3N4 obtained a stronger symmetric resonance signal, confirming the presence of unpaired electrons and nitrogen vacancies on the aromatic ring carbon atoms. This indicates that during the high-temperature polymerization of urea, KOH is added to the g-C3N4 matrix to form nitrogen defects, thereby enhancing the light absorption ability.

[0067] like Figure 5 As shown, it can be observed in the ultraviolet diffuse reflectance spectrum of Dy2O3-5%CN-x (x represents 0.02, 0.04, 0.06, 0.08, 0.1) that when the doping amount of ND-g-C3N4 is only 5%, compared with the other samples, the absorption peak of Dy2O3-5%CN-0.06 is significantly red-shifted compared with Dy2O3, and the band gap width is also reduced from 4.85eV to 4.75eV. This shows that doping CN-0.06 has a greater impact on the light absorption range of Dy2O3. Therefore, CN-0.06 and Dy2O3 are selected to prepare Dy2O3 / ND-g-C3N4 composite catalyst. Wherein, in the specification and drawings of the present invention, CN represents ND-g-C3N4.

[0068] like Figure 6 As shown in the UV diffuse reflectance spectrum of Dy2O3, it can be seen that Dy2O3 has absorption peaks at 349nm, 363nm, 385nm, 424nm, 450nm, and 473nm, in addition to the absorption peak at 230nm, corresponding to 6H 15 / 2 Ground state to 6P 7 / 2 , 6P 5 / 2 , 4F 7 / 2 +4I 13 / 2 , 4G 11 / 2 , 4I 15 / 2 , 4F 9 / 2 The UV diffuse reflectance spectrum of the prepared catalyst shows that with the increase of the amount of CN-0.06 added, the absorption peak of the prepared catalyst red-shifts. When the doping amount is 20%, 25% and 30%, the absorption peak of the prepared catalyst moves significantly to the visible light region. Figure 4It can be seen that the bandgap width of the prepared catalyst gradually decreases with the increase of CN-0.06. Among them, the prepared catalyst Dy2O3-25%CN-0.06 has the smallest bandgap width (2.62eV), which is 2.23eV smaller than pure Dy2O3 (4.85eV). The experimental results show that CN-0.06 can effectively reduce the bandgap width of Dy2O3 and broaden the light response range, thereby generating more photogenerated carriers, which helps to improve the efficiency of photocatalytic hydrogen production.

[0069] like Figure 7 As shown, compared with pure Dy2O3, the hydrogen production rate of the prepared catalyst Dy2O3-5%CN-x increased. Among the prepared catalysts, the mass fraction of ND-g-C3N4 was 5%, and the sample marked Dy2O3-5%CN-0.06 had the largest hydrogen production rate, indicating that there was an optimal KOH doping amount when preparing ND-g-C3N4.

[0070] like Figure 8 As shown, compared with pure Dy2O3, the hydrogen production rate of the prepared catalyst Dy2O3 / ND-g-C3N4 is significantly increased. Among them, the mass ratio of nitrogen-deficient graphite phase carbon nitride to dysprosium oxide is 1:3, that is, the mass fraction of ND-g-C3N4 in the prepared catalyst is 25%, and the sample marked as Dy2O3-25%CN-0.06 has the highest hydrogen production rate. This shows that after adding ND-g-C3N4, the light response range of Dy2O3 is broadened, and the absorption of visible light by the prepared catalyst is increased. In addition, the loaded ND-g-C3N4 can form a heterojunction with Dy2O3, effectively reducing the recombination rate of photogenerated carriers and increasing the rate of photocatalytic hydrogen production reaction. However, when the ND-g-C3N4 loading is 30%, the hydrogen production efficiency of the prepared catalyst decreases significantly. This can be attributed to the fact that too much ND-g-C3N4 covers the active reaction sites distributed on the Dy2O3 surface and blocks part of the incident visible light, thereby reducing the photocatalytic activity of the system. Therefore, there is an optimal loading ratio of ND-g-C3N4.

[0071] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A method for preparing a dysprosium oxide / nitrogen-deficient graphite-phase carbon nitride visible light photocatalyst, characterized in that: The specific steps include: (1) Preparation of modified nitrogen-deficient graphite carbon nitride: urea was dissolved in a certain volume of KOH aqueous solution, with the mass ratio of KOH to urea being 2-10:750, and then dried in an oven at 60°C; The dried mixture was transferred to a crucible, calcined in a muffle furnace, cooled to room temperature naturally, washed three times with anhydrous ethanol and deionized water respectively, and placed in a vacuum drying oven to obtain modified nitrogen-deficient graphite phase carbon nitride; (2) Preparing a nitrogen-deficient graphite phase carbon nitride suspension: placing the nitrogen-deficient graphite phase carbon nitride obtained in step (1) in deionized water, and dispersing it evenly by ultrasonication to obtain a nitrogen-deficient graphite phase carbon nitride suspension; (3) Mixing: Add dysprosium oxide to the nitrogen-deficient graphite phase carbon nitride suspension, stir the mixture by ultrasonic stirring to make it uniform, and then place it in a vacuum drying oven to obtain a solid substance; The mass ratio of nitrogen-deficient graphite phase carbon nitride to dysprosium oxide used is 1:2~19; (4) Preparation of dysprosium oxide / graphite-phase carbon nitride photocatalyst by calcination method: The solid material obtained in step (3) is transferred to a porcelain boat and calcined in a tube furnace to obtain a dysprosium oxide / nitrogen-deficient graphite-phase carbon nitride visible light catalyst; Among them, the heating rate of the tubular furnace is 5°C / min, the roasting temperature is 500°C, and the roasting time is 3h; In the prepared dysprosium oxide / nitrogen-deficient graphite-phase carbon nitride visible light photocatalyst, the mass percentage of nitrogen-deficient graphite-phase carbon nitride is 20-30%.

2. The method for preparing a dysprosium oxide / nitrogen-deficient graphite-phase carbon nitride visible light photocatalyst according to claim 1, characterized in that: The mass ratio of KOH to urea is 6:

750.

3. The method for preparing a dysprosium oxide / nitrogen-deficient graphite-phase carbon nitride visible light photocatalyst according to claim 1, characterized in that: In the step (1), the volume ratio of the urea to the KOH aqueous solution is 7.5 / 50 g / ml.

4. The method for preparing a dysprosium oxide / nitrogen-deficient graphite-phase carbon nitride visible light photocatalyst according to claim 1, characterized in that: In the step (1), the calcination temperature is 550°C, the calcination time is 3 hours, the heating rate is 5°C / min, and the vacuum drying temperature is 55°C.

Citation Information

Patent Citations

  • Nitrogen-containing vacancy carbon nitride photocatalyst as well as preparation method and application thereof

    CN113731464A